2019
DOI: 10.5507/ag.2018.025
|View full text |Cite
|
Sign up to set email alerts
|

Physical self-esteem of wheelchair basketball players

Abstract: Whitehead, & Eklund, 2012), it is influenced by people's perceptions across different domains. One of these important domains is physical self-esteem (Fox & Corbin, 1989) that can be described as a multidimensional hierarchical subjective perception and affective evaluation of people's various physical traits. The physical self has been considered as one of the most important factors correlated to global selfesteem throughout all ages (Fox, 2000). Moreover, Harter (2012) reported that perceptions of physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Currently, wheelchair basketball is one of the adapted sports studied by researchers from different fields such as: physiology (Antonelli et al, 2020;Barboza et al, 2019;Conners et al, 2020;Feter et al, 2018;Galea et al, 2018;Marzsalek et al, 2019;Peters et al, 2020), biomechanics (de Witte et al, 2016;Marjolaine et al, 2018;Sasadai et al, 2020;Zacharakis, 2020), medicine (Hollander et al 2020), motor skills (Maksym et al 2018;de Witte et al, 2018), psychology (Qasim et al, 2019;Yeats et al, 2019), or sociology (Molik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, wheelchair basketball is one of the adapted sports studied by researchers from different fields such as: physiology (Antonelli et al, 2020;Barboza et al, 2019;Conners et al, 2020;Feter et al, 2018;Galea et al, 2018;Marzsalek et al, 2019;Peters et al, 2020), biomechanics (de Witte et al, 2016;Marjolaine et al, 2018;Sasadai et al, 2020;Zacharakis, 2020), medicine (Hollander et al 2020), motor skills (Maksym et al 2018;de Witte et al, 2018), psychology (Qasim et al, 2019;Yeats et al, 2019), or sociology (Molik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In WB each player is classified by functional class (from 1.0 to 4.5), whereby the lower the functional class, the greater the athlete's motor limitation; the technical team should take the functional classification into account when choosing the initial five players, since it cannot exceed a total of 14 points. 5,6 WB is one of the adapted sports that has been the subject of examination by research in a range of areas, including physiology, 7,8 training and sports performance, 9,10 biomechanics, 11,12 psychology, 13,14 or sociology. 15,16 There are also match analyses being carried out on WB, [17][18][19][20][21] some of which incorporate the players' functional class, as this work does.…”
Section: Introductionmentioning
confidence: 99%
“…WB is one of the adapted sports that has been the subject of examination by research in a range of areas, including physiology, 7,8 training and sports performance, 9,10 biomechanics, 11,12 psychology, 13,14 or sociology. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Human Kinetics -volume 81/2022 http://www.johk.pl biomechanics (Marjolaine et al, 2018), physiology (Marszałek et al, 2019), physiotherapy (Veeger et al, 2019), motor skills (de Witte et al, 2018), psychology (Qasim et al, 2019), and sociology (Molik et al, 2017). Match analysis studies have also been conducted in wheelchair basketball (Francis et al, 2019a(Francis et al, , 2019bGómez et al, 2014), and studies which have investigated the influence of functional ability on performance by male (Skučas et al, 2009) and female (Vanlandewijck et al, 2004) players have reported comparable performance levels between similar functional categories.…”
Section: Introductionmentioning
confidence: 99%
“…Although Paralympic sports are still a long way from attracting the level of research interest enjoyed by elite sport, numerous aspects of wheelchair basketball have been analyzed in recent years ( Perret, 2017 ), including biomechanics ( Marjolaine et al, 2018 ), physiology ( Marszałek et al, 2019 ), physiotherapy ( Veeger et al, 2019 ), motor skills ( de Witte et al, 2018 ), psychology ( Qasim et al, 2019 ), and sociology ( Molik et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%